Analisa untuk Pengembangan E-Learning Universitas X pada Pasca Pandemi - Sutoyo, Mochammad Arief Hermawan Sutoyo; Setiawan, Roby (LPPM Universitas Dinamika Bangsa, 2023)
After the pandemic, the use of e-learning was not mandatory at University X, due to the return to offline lectures, so that the use of applications that had been built were not used optimally as the EDMODO application which was used previously as University X's e-learning system. This change in conditions did not only occur in X University but also elsewhere. This change in conditions has led to the need for research related to the impact of post-pandemic use on e-learning that is currently used by students and lecturers at University X. This research was conducted quantitatively using a questionnaire with a system usability scale instrument with respondents from the academic community at University X. Based on the calculations made the value of SUS e-learning at University X was 68.97. This value states that the system currently used is categorized as good enough. However, the SUS value of the e-learning system currently used is lower than the value obtained in previous studies using EDMODO as an e-learning application.